How to Avoid the Usual Price Rule on the Fuel Market in the Czech Republic - Pavel Semerád (Acta Universitatis Agriculturae et Silviculturae Mendelianae Brunensis, 2016)
The paper deals with value added tax evasions on the fuel market in the Czech Republic. This commodity is used in carousel fraud. In the chains of taxpayers there are missing traders who fail to meet their tax obligations. Their business strategy is based on quick sales at unusually low prices which do not allow honest parties to compete. Tax administrators should focus on unusual prices which constitute a higher probability of tax evasions. This paper aims to verify whether or not there are ways to evade the measure, focusing specifically on applying methods which could help achieve lower sales prices while avoiding the possibility to require unpaid tax from the recipients of taxable supply. The weaknesses thus found are described and demonstrated in more detail in the paper. During a research some ways were found which could be used for avoiding this specific measure. Methods of Cash Back and Free Shipping were identified and described.